Hubungan Antara Kecemasan dengan Keluhan Nyeri Ulu Hati pada Pasien Rawat Jalan di Poli Penyakit Dalam RSD. dr. Soebandi - Puspita Sari; Alif Mardijana; Azham Purwandhono (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Anxiety is a tension, insecurity and fears that arise because of feeling that something bad will happen, it is one of psychiatric disorder causing a somatization disorder. A common somatization disorder is an epigastric pain. Epigastric pain is subjective physical complaint located at the epigastric region. This study aimed to determine whether there was a correlation between anxiety and epigastric pain symptom on outpatients of Internal Medicine dr. Soebandi hospital. This was an observational analytic study with cross sectional approach. Measurement of anxiety level using questionnaires HARS ( Hamilton Anxiety Rating Scale ) and pain level measurements using questionnaires VAS ( Visual Analog Scale ). Data was obtained using questionnaires by interview technique. The result showed a significant relationship ( p = 0.000 ) between the anxiety and epigastric pain symptom. Analysis of the relationship between the two variables showed a positive correlation 0.688. In conclusion, there was a positive correlation between anxiety-disorders and epigastric pain symptom. Keywords: anxiety, epigastric pain, HARS, VAS